Prevalence of Visual Impairment Among School Children in Lengkong Subdistrict Bandung - Rachmawati, Dinta; Raden Roro, Annisa Wahyuni Ratnasari; Amiruddin, Primawita Oktarima (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2025)
Visual impairment in children still becomes a burden globally. It can affect children’s learning process, career options, and psychosocial development eventually. This study aims to determine the prevalence of visual impairment among schoolchildren in Lengkong Subdistrict, Bandung. This was a retrospective descriptive study using secondary data from visual impairment screening program of schoolchildren aged 6-14 years, which was conducted by Health Promotion Unit of Bandung Eye Center Hospital from August to November 2023. The sample for this study was collected using a total sampling technique. A total of 907 data consisting of Uncorrected Visual Acuity (UCVA), Presenting Visual Acuity (PVA), age, and gender were collected and analysed using Microsoft Excel 2019. The prevalence of visual impairment in schoolchildren was 16.2% with UCVA and 11.1% with PVA, moderate visual impairment was the major classification. Female students were more likely to have visual impairment compared to male students. The highest number of visual impairments with UCVA and PVA compared to age distribution was 12 years old. These results need to become school and government’s concern to create further policy regarding children’s eye health to support an optimal learning process.